Green synthesized Zingiber officinale-ZnO nanoparticles: anticancer efficacy against 3D breast cancer model - Ruqaya Alhaddad; Bassam M Abualsoud; Ibrahim Al-Deeb; Hamdi Nsairat (Future Science OA, 2024)
Aim: ZnO NPs were prepared via green synthesis utilizing Zingiber Officinale.Methodology: Physical characterization and biological activity were performed against 2D, and 3D spheroids MCF-7 cell lines.Results: The NPs exhibited 188.9, 175.7 and 171.2 nm size with charge of -8.2, -11.7 and -9.7 mV for the 2%, 3% and 4% formulations. XRD confirmed a wurtzite hexagonal phase. FTIR spectra showed Zn-O stretching vibrations. The 2%, 3% and 4% formulations presented IC50 values of 14.7, 26.2 and 47 μg/ml, respectively, with complete destruction of MCF-7 spheroids. Elevated TNF-α levels suggested an inflammatory-mediated mechanism of action.Conclusion: 2% Zingiber officinale-derived ZnO NPs showed antitumor potential against deserving further mechanistic and in vivo explorations.